PERKEMBANGAN GARAP GENDING JANGKUNG KUNING - Sugimin Sugimin (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2014)
Gending Jangkung Kuning is one of the repertoire gending Karawitan Surakarta style that has been developing of musical garap. With the ability of creativity, the pengrawit use the wealth of the musical vocabuler such as rhythm, cengkok, dynamics, vocals, and instruments, the has been developed to become a variety of gending Jangkung Kuning. Till now there are three plots gending Jangkung Kuning, Jangkung Kuning as gending klenengan Surakarta style, as golek Dance musical style Yogyakarta and as garap gending klenengan Ki Nartasabdha. The occurrence of variety gending Jangkung kuning, caused by factors other than the creativity of artists, is also caused by other factors, such as the interpretation of garap, cultural environment, serving functions, as well as figure pengrawit. Gending Jangkung Kuning of Yogyakarta style is a reinterpretation of the gending Jankung Kuning Surakarta style. The development is strongly colored by the culture that flourished in Karawitan Yogyakarta style, namely a change of balungan mlaku become balungan ngracik. Ki Nartasabdha to develop on rhythm interpretation and vocals interpretation making gending Jangkung Kuning create an impression of the new flavors. With the advent of a variety of gending Jangkung Kuning, then gending is increasingly popular and is known by the musicians.Keywords: development, garap, gending Jangkung Kuning, Ki Nartasabdha